Inherited and acquired corona of coronavirus in the host: Inspiration from the biomolecular corona of nanoparticles. (August 2021) - Gao, Jie; Zeng, Li; Yao, Linlin; Wang, Ziniu; Yang, Xiaoxi; Shi, Jianbo; Hu, Ligang; Liu, Qian; Chen, Chunying; Xia, Tian; Qu, Guangbo; Zhang, Xian-En; et al.
Highlights: Coronaviruses could interact with biological molecules in biological fluids of the host to form "an acquired corona". The acquired corona might be a player in the interaction of viruses with host cells. It is imperative to characterize the biomolecular components of acquired corona and the formation mechanisms. Graphical Abstract: ga1 Abstract: The family of coronavirus are named for their crown shape. Encoded by the genetic material inherited from the coronavirus itself, this intrinsic well-known "viral corona" is considered an "inherited corona". After contact with mucosa or the entrance into the host, bare coronaviruses can become covered by a group of dissolved biomolecules to form one or multiple layers of biomolecules. The layers acquired from the surrounding environment are named the "acquired corona". We highlight here the possible role of the acquired corona in the pathogenesis of coronaviruses, which will generate fresh insight into the nature of various coronavirus-host interactions.